2021
DOI: 10.1039/d0tc04407e
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances and prospects of D1:D2:A non-fullerene ternary polymer solar cells

Abstract: Ternary polymer solar cells (PSCs) exhibit broader absorption band, greater poternial in micro-morphology regulation, energy level tuning, and other advantages compared with binary PSCs and is a facile and efficient...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 175 publications
0
15
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] To date, many attempts have been made to obtain efficient PSCs and a lot of effort has been put into them, including interfacial engineering, study of novel donor/acceptor materials, and optimizing the morphology. [19][20][21][22][23][24][25][26][27][28][29][30][31][32] By now, the power conversion efficiency (PCE) of PSCs has exceeded 19%. [33] During the development of PSCs, interfacial engineering has received a lot of attention for its ability to improve the photovoltaic parameters of PSCs and thus improve PCE.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] To date, many attempts have been made to obtain efficient PSCs and a lot of effort has been put into them, including interfacial engineering, study of novel donor/acceptor materials, and optimizing the morphology. [19][20][21][22][23][24][25][26][27][28][29][30][31][32] By now, the power conversion efficiency (PCE) of PSCs has exceeded 19%. [33] During the development of PSCs, interfacial engineering has received a lot of attention for its ability to improve the photovoltaic parameters of PSCs and thus improve PCE.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1–18 ] To date, many attempts have been made to obtain efficient PSCs and a lot of effort has been put into them, including interfacial engineering, study of novel donor/acceptor materials, and optimizing the morphology. [ 19–32 ] By now, the power conversion efficiency (PCE) of PSCs has exceeded 19%. [ 33 ]…”
Section: Introductionmentioning
confidence: 99%
“…Fullerenes have some undesirable characteristics in OPVs such as their low light absorption coefficients in the visible and near infrared region, their general aggregation which causes them to crystallize resulting in poor device stability, and their lack of structural tunability. 5 This has led to the investigation of many other small molecules [6][7][8] and polymers [9][10][11][12] with electronic properties to address the gaps from fullerenes, which include synthetic methodologies for the formation of non-fullerene small molecules as electron-acceptors that have activity in the visible light and near infrared region and studies have shown diverse synthetic versatility for fullerene alternatives. [6][7][8] As examples of small molecules, boron subphthalocyanines (BsubPcs, Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In order to evaluate the impact of the green additive EHB and processing solvent O‐XY on the morphology of the thin films, we characterized the information on the surface and inside of the films using AFM [ 29–36 ] and TEM, and they were exhibited in Figure . As seen in Figure 3a,b, the root mean square value (RMS) of the devices treated with 3% EHB is 0.88 nm, which is smaller than the without additives device (1.58 nm), the smaller RMS, the lower roughness of the blend film, probably due to the 3% EHB additives making the surface of the blend film more uniform, which contributes to the establishment of a good interpenetrating network structure, promoting dissociation of excitons, and providing a pass‐through path for charge transport.…”
Section: Resultsmentioning
confidence: 99%